Resveratrol Enhances Cytotoxic Effects of Cisplatin by Inducing Cell Cycle Arrest and Apoptosis in Ovarian Adenocarcinoma SKOV-3 Cells through Activating the p38 MAPK and Suppressing AKT - Phateep Hankittichai; Phatarawat Thaklaewphan; Nitwara Wikan; Jirapak Ruttanapattanakul; Saranyapin Potikanond; Duncan R. Smith; Wutigri Nimlamool (MDPI AG, 2023)
In the current study, we identified a mechanism of resveratrol (RES) underlying its anti-cancer properties against human ovarian adenocarcinoma SKOV-3 cells. We investigated its anti-proliferative and apoptosis-inducing effects in combination with cisplatin, using cell viability assay, flow cytometry, immunofluorescence study and Western blot analysis. We discovered that RES suppressed cancer cell proliferation and stimulated apoptosis, especially when combined with cisplatin. This compound also inhibited SKOV-3 cell survival, which may partly be due to its potential to inhibit protein kinase B (AKT) phosphorylation and induce the S-phase cell cycle arrest. RES in combination with cisplatin strongly induced cancer cell apoptosis through activating the caspase-dependent cascade, which was associated with its ability to stimulate nuclear phosphorylation of p38 mitogen-activated protein kinase (MAPK), well recognized to be involved in transducing environmental stress signals. RES-induced p38 phosphorylation was very specific, and the activation status of extracellular signal-regulated kinase 1/2 (ERK1/2) and c-Jun N-terminal kinase (JNK) was not mainly affected. Taken together, our study provides accumulated evidence that RES represses proliferation and promotes apoptosis in SKOV-3 ovarian cancer cells through activating the p38 MAPK pathway. It is interesting that this active compound may be used as an effective agent to sensitize ovarian cancer to apoptosis induced by standard chemotherapies.